The Earth through alien eyes. (1st August 2022) - Romero, James
Abstract : Aliens spying on us from across interstellar space is a classic trope of science fiction. But working out what those extraterrestrials might see if they pointed their telescopes at us could help in our quest for finding life on distant Earth-like planets, as James Romero explains.